Making Trade an Engine of Growth for All : The Case for Trade and for Policies to Facilitate Adjustment. (Policy Papers; Policy Paper, 2017)
The role of trade in the global economy is at a critical juncture. Increased trade integration helped to drive economic growth in advanced and developing economies in the latter part of the 20th century. Since the early 2000's, however, a slowdown in the pace of trade reform, a post-crisis uptick in protectionism, and risk of further reversals have been a drag on trade, productivity, and income growth. At the same time, trade is leaving too many individuals and communities behind, notably also in advanced economies. To be sure, job losses in certain sectors or regions in advanced economies have resulted to a large extent from technological changes rather than from trade. But adjustment to trade can bring a human and economic downside that is frequently concentrated, sometimes harsh, and has too often become prolonged. It need not be that way. With the right policies, countries can benefit from the great opportunities that trade brings and lift up those who have been left behind. Those polices ease adjustment to trade, as well as strengthen overall economic flexibility and performance.